Skills of the nursing team regarding palliative care in patients with cervical cancer (Research, Society and Development, 2021)
Conduct a literature search on the main competencies of the nursing team through palliative care in patients with cervical cancer, jointly addressing their main conducts and difficulties. This is a descriptive, exploratory study, with a qualitative approach, using the Integrative Literature Review (RIL) as a technique. For data collection, the databases available and indexed within the Virtual Health Library were used: SCIELO, LILACS, BDENF and MEDLINE, by joining three Health Descriptors, crossed with the Boolean operator "AND": Palliative Care AND Cervical Neoplasms AND Nursing Care. 236 articles were found in total, after applying the inclusion and exclusion criteria, 13 articles were selected. The researches addressed the importance of the nurse through the guidance of palliative care, emphasizing that correct communication is essential so that it is possible to teach them to deal with changes, reinforcing dialogues so that it is possible to alleviate isolation and fear, reinforcing the importance of family support. Due to the various difficulties presented by these professionals, a self-reflection on this theme is extremely important, thus contributing not only to care practice, but also to a better quality of life for the family and those assisted.